(untitled) (The Pakistan Development Review, 2006)
A standard gravity model was applied to estimate the magnitude of potential trade flows between Pakistan and the nine ECO member countries. The major issue in this analysis is to explore that Intra- ECO trade has great potential for Pakistan and that it got lower share than its potential. The results from the gravity model confirm that ECO has a positive and significant impact on intra-regional trade. It suggests that intra-regional trade is lower than what would be predicted by the gravity equation, suggesting greater scope for regional integration among the ECO member countries. This is especially the case between countries that have a common geographical border. The privilege of geography and the existence of trade preferences among ECO members could be expanded to cover potential trade to neighboring countries.